Tingkah Laku Buli Dan Hubungannya Dengan Harga Diri Pelajar Di Empat Buah Sekolah Menengah Harian Daerah Kuala Muda, Yan, Kedah - Hashim, Ismail (2001)

(untitled)
The purpose of this study is to describe bullying behavior and determine its relationship with students' self-esteem according to form and gender in four daily secondary schools in the Kuala Muda, Yan District. The dimensions of bullying being studied were indirect and direct bullying and victims of direct and indirect bullying. Socialization factors that were related to students' behavior comprised interaction with adults, influence of peer group and the environment. It is also the purpose of this study to determine the relationship between dimensions of bullying behavior and socialization with students' self-esteem. The sampel of the study consisted of 500 form two and form four students from four Grade A secondary schools. Pearson Correlation (r), t-test and one-way ANOVA were used to analyze the data. The results showed that bullying incidents occurred mainly in the classrooms. More boys were involved in bullying compared to girls and the occurrence is more of indirect bullying. Generally, the incidence of bullying was low. Results of T-test showed significant differences in (i) indirect bullying according to gender (ii) victims of indirect bullying according to form (iii) victims of indirect bullying according to gender and (iv) indirect bullying according to category of school. The results for ANOVA showed significant difference between bullying and the victims of direct bullying according to school. Peer group influence was more significant in determining bullying and victims of bullying compared to adult and environmental factors. Result of correlation analysis showed self-esteem was not significantly related with bullying and victims of bullying. A total 27.4% of the respondents belonged to the high self-esteem group compared to 0.6% who belonged to the lower self-esteem group.